SOSIALISASI DAN EDUKASI HUKUM KESEHATAN TENTANG PERTANGGUNGJAWABAN TENAGA MEDIS ATAS RISIKO MEDIS DALAM PELAYANAN KESEHATAN BAGI MASYARAKAT DESA BAGIK POLAK - Khairunisyah; Adhar; Lalu Kesa Rahmatullah; Rahmad Hidayah; Yulia Nurrahmawati; Muhammad Aditya Rachman; Sri Rahmawati (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2026)
This community service program aims to enhance public understanding of the legal accountability of medical personnel regarding medical risks in healthcare services while also strengthening awareness of healthy living practices in Bagik Polak Village. The primary issue faced by the community is the low level of health law literacy, particularly in distinguishing between medical risks and malpractice, which often leads to misunderstandings toward medical personnel. The implementation method employed a socialization and educational approach through stages of preparation, execution, evaluation, and follow-up. The program involved lecturers from Universitas Bima Internasional MFH, medical personnel from Bagik Polak Community Health Center, village authorities, and local community members. The materials delivered included health law education, medical risks, malpractice, healthy lifestyle practices, and basic health consultations. The results demonstrated an improvement in community understanding of the differences between medical risks and malpractice, increased health law awareness, and strengthened public trust in medical personnel and the healthcare system. Furthermore, the program successfully encouraged behavioral changes toward healthier lifestyles. Therefore, this community service activity proved effective as a means of community empowerment through preventive health law education and contributed to fostering a more harmonious relationship between the community and medical personnel.